An Object-Oriented Approach for the Recursive Numeration and Visualization of the Key Strata of Coal Mines - Xu, Chun; Zhou, Keping; Xiong, Xin; Lu, Yan (Frontiers in Earth Science, 2021)
The exploitation and utilization of coal resources have caused serious ecological and environmental problems that are closely related to the movement and destruction of the overlying strata, especially the activities of the overlying key strata (KS). The existing KS calculation methods are characterized by low efficiency and high costs. This study proposes an object-oriented improved recursive algorithm (OORA) model to a9chieve efficient calculations for KS. An application program was developed and tested with the KS of Xiadian coal mine, Shanxi, China. The calculation results were basically consistent with field observations, and the calculation depth was increased by 146.05m. In addition, five typical KS calculation cases were selected for in-depth testing. The calculation time ranged from 0.175–0.225 seconds, and the calculation time was shortened by approximately 3 times compared to that with traditional methods. Therefore, it is feasible to apply the model algorithm for KS calculations, and the model provides benefits such as high efficiency and low costs.